Dear Levi : letters from the Overland Trail - Woodruff, Elvira; Peck, Beth (New York : Knopf : Distributed by Random House, 1998)
Twelve-year-old Austin Ives writes letters to his younger brother describing his three-thousand-mile journey from their home in Pennsylvania to Oregon in 1851.
G9
Keywords: Overland journeys to the Pacific -- Fiction; Frontier and pioneer life -- Fiction; Letters -- Fiction; Historical fiction